DAMPAK NILAI FINAL TERHADAP KINERJA DOSEN DALAM PERSPEKTIF MAHASISWA AKUNTANSI - Mariadi, Yusli; Isnawati, Isnawati; Isnaini, Zuhrotul (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
The lecturer performance appraisal in lectures was conducted by distributing questionnaires to find out the opinions of students during the lectures conducted. Assessment is carried out on 10 (ten) elements with the rating scale used 1 – 5. The assessment of students on lecturer performance show different results for the same lecturer in each semester. This fact raises questions in the mind of the author with the differences in the results of this assessment. Is there anything (factor) that affects the difference in the results of this assessment, such as giving Final Values ​​by lecturers to students. So that students who judge lecturers who give them good grades will give a good assessment to the lecturers in question, and vice versa will give a bad value for lecturers who describe the final value that is less satisfying for the students concerned. But the results of the study show that the final score did not have a significant impact on the assessment of student performance towards the lecturer. This is possible because the assessment data provided by students does not show the actual assessment, both the data before and after the final score.